PENERAPAN TEKNOLOGI BUDIDAYA TANAMAN JAHE DI NAGARI TAEH BARUAH KECAMATAN PAYAKUMBUH KABUPATEN LIMAPULUH KOTA - Yulmira Yanti; Irwin Mirza Umami; Lora Triana; Noveriza Hermeria (Jurnal Hilirisasi IPTEKS, 2021)
Nagari VIII Koto is one of the villages in Guguak District with agriculture as the main economic sector of the community with the main crops of lowland rice and maize. Access to remote provincial and regency capitals is one of the obstacles to economic growth for these regions. There is often a shortage of fertilizers because subsidized fertilizers are lost on the market, making it difficult for farmers to maintain their production. The solutions that can be offered are planting ginger plants that are more resistant to drought, processing agricultural waste into compost, an alternative to reduce dependence on the use of chemical fertilizers, use of biological agents and vegetable pesticides as agents for controlling pests and diseases, and processing ginger production for increase selling value, competitiveness and community income. The purpose of this farmer group empowerment activity is to increase farmers' interest in cultivating ginger well and towards certification of better cultivation (healthy and organic) and processing ginger into instant products independently by the village community. The method used in this activity is socialization and counseling activities. The results obtained from this activity, the community and farmers get new understanding and knowledge about how to cultivate ginger plants properly and correctly and how to process ginger into a higher quality product, have higher competitiveness and will be able to compete in the international arena because of its benefits. many in the world of health. The conclusion of this activity is to increase the understanding of the community, especially farmers in ginger cultivation activities, and increase the interest of farmers in processing ginger into quality products.